2020
DOI: 10.1021/acsphotonics.0c00491
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed p-Type Copper Thiocyanate (CuSCN) Enhanced Sensitivity of PbS-Quantum-Dots-Based Photodiode

Abstract: Lead sulfide (PbS) quantum dots (QDs) exhibit outstanding size-dependent properties that can be harnessed for optoelectronic applications. For example, they can be used for broadband light detection thanks to their band gap, which can be tuned from the UV to near-infrared. Recent reports show that reducing the dark current in PbS-QDs-based photodetectors leads to improved performance. To this end, we explore the use of low-cost solution-processed p-type copper thiocyanate (CuSCN) films as hole-transporting lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In Equation 3, V is the applied voltage across the two electrodes of the photodiode, d the thickness of the photoactive layer, and μ e and μ h the electron and hole mobilities, respectively. In most solution-processed NIR PDs, d is at least a few hundreds of nanometers in order to achieve sufficient light absorption, [7,15,36] and their f −3dB values would thus be limited by the long transit distances required. In addition, organic PDs suffer from low or unbalanced charge-carrier [29,44] which could further lower their f −3dB values, since charge-carrier transport will be limited by the smallest charge-carrier mobility.…”
Section: Rationalizing the Fast Response Of Agbis 2 Pdsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Equation 3, V is the applied voltage across the two electrodes of the photodiode, d the thickness of the photoactive layer, and μ e and μ h the electron and hole mobilities, respectively. In most solution-processed NIR PDs, d is at least a few hundreds of nanometers in order to achieve sufficient light absorption, [7,15,36] and their f −3dB values would thus be limited by the long transit distances required. In addition, organic PDs suffer from low or unbalanced charge-carrier [29,44] which could further lower their f −3dB values, since charge-carrier transport will be limited by the smallest charge-carrier mobility.…”
Section: Rationalizing the Fast Response Of Agbis 2 Pdsmentioning
confidence: 99%
“…However, silicon-based PDs are usually bulky and require sophisticated manufacturing processes, making them less attractive as portable or wearable devices. On the other hand, organic materials, [10][11][12] lead-halide perovskites, [7,13] and chalcogenide quantum dots (QDs) [14][15][16] have demonstrated higher absorption coefficients in the NIR region than silicon, and their solution processability at low temperatures enables them to be compatible with polymer substrates, which are ideal for flexible and lightweight electronics. Nevertheless, NIR PDs based on these materials also face various challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of CH3NH3PbI3 enabled PbS CQDs to generate greater gains. To further reduce the dark current of the device, in 2020, Ka et al reported a strategy combining copper thiocyanate (CuSCN) and PbS CQDs to reduce the dark current of PbS CQD-based photodetectors [73] (Figure 8h,i). The detectivity of the prepared photodiode could reach 10 11 Jones.…”
Section: Pbs Cqd Photodetectorsmentioning
confidence: 99%